Body Image and Disordered Eating Among LGBTQ+ University Students and Recent Graduates in Rural Appalachia: A Thematic Analysis - Savitsky, Devyn (Universitas Negeri Yogyakarta, 2021)
LGBTQ+ university students and recent graduates of a large rural Appalachian institution were interviewed for an exploratory thematic analysis on body image and disordered eating behaviors. While participants noted an overall sense of comfortability in the university setting, there were varying obstacles associated with navigating intersecting identities and physical presentation that were noted in the data. Excerpts from participant interviews were coded into five unique themes: (1) feeling